Randomized clinical trial to evaluate ferric carboxymaltose and iron sucrose for treatment of postpartum anaemia in a tertiary hospital - H. S., Sheela; Neelakanthi, Ashwini; C. P., Nikitha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Ferric carboxymaltose and iron sucrose are two iron carbohydrate complexes optimized for iron delivery and extensively used in postpartum anaemia. This study compares the efficacy and safety of ferric carboxymaltose with that of iron sucrose in patients with postpartum anaemia. Methods: One hundred women diagnosed with postpartum anaemia were randomized prospectively in a 1:1 ratio to receive either ferric carboxymaltose or iron sucrose. Fifty patients received intravenous iron carboxymaltose depending on the iron deficit at rate of 1000 mg/week and fifty patients received intravenous iron sucrose at a rate of 200 mg/day on alternate days till the calculated dose is given. Results: Fifty patients were enrolled in each treatment group. Both groups showed increases in mean haemoglobin from baseline at 2 weeks and 6 weeks. The increase in haemoglobin was significantly higher in ferric carboxymaltose group compared to iron sucrose at both week 2 (2.64±0.91 versus 2.17±0.76; p=0.010) and week 6 timepoints (4.65±1.17 versus 3.96±1.06; p=0.005). The proportion of patients achieving target haemoglobin of 12 gm/dl was significantly higher in ferric carboxymaltose group compared to iron sucrose at week 6 (77.3% versus 50.0%; p=0.013). The incidence of adverse events was similar across treatment groups and no specific safety concerns were observed. Conclusions: Both ferric carboxymaltose and iron sucrose caused increase in baseline haemoglobin. Ferric carboxymaltose had significantly higher increases in haemoglobin compared to iron sucrose at both follow up timepoints (week 2 and week 6). It was more likely to achieve target haemoglobin with ferric carboxymaltose within 6 weeks compared to iron sucrose. Ferric carboxymaltose may be considered in women with postpartum anaemia for faster rise in haemoglobin while requiring fewer injections compared to iron sucrose.